Axially Ligated Zirconium(IV) Tetraphenylporphyrin: Synthesis, Characterization, and Biological Activity. (13th October 2014) - Bajju, Gauri D.; Anand, Sunil Kumar; Devi, Gita
Abstract : A series of 5, 10, 15, 20-tetraphenylporphinatozirconium(IV) acetylacetonatophenolates containing different phenols as axial ligands [Zr(TPP)(Y)(X)] (TPP = 5, 10.15, 20-tetraphenyl-21H, 23H-porphine; Y = acac; X = different phenolates) have been synthesized and characterized by various spectrochemical studies. The complexes were also screened for antimicrobial activities. Antifungal activity of some adducts has been carried out against the fungal strain Sclerotium rolfsii. Most of the complexes have shown good antibacterial activity.